Extraction of α-glucosidase inhibitory compounds from Phaleria macrocarpa fruit flesh using solvent, sonication, and subcritical carbon dioxide soxhlet methods - Easmin, Sabina; Sarker, Md. Zaidul Islam; Ghafoor, Kashif; Ferdosh, Sahena; Jaffri, J. M.; Akanda, Md. Jahurul Haque; Al-Juhaimi, Fahad Y.; Bostanudin, M. Fauzi; Khatib, Alfi (Wiley-Blackwell Publishing Ltd, 2017)
The objective of this study was to compare a-glucosidase inhibitory activity of Phaleria macrocarpa extracts using subcritical carbon dioxide (subCO2) soxhlet extraction method with sonication and solvent extraction methods. The extraction was performed by subCO2 soxlet using carbon dioxide and the conventional organic solvent-based sonication using ethanol and water, solvent extraction using methanol, and n-hexane solvents. The yields and a-glucosidase inhibitory activity of the P. macrocarpa extracts were analyzed. The yields using sonication, solvent extraction, and subCO2 soxhlet extraction were approximately 10.261.0 to 25.460.6% and 0.960.1 to 2.061.0%. The IC50 value of subCO2 soxhlet, sonication, and solvent extraction methods were 4.35, 7.34, and 1.9 mg/mL, respectively. The a-glucosidase inhibitory activity of P. macrocarpa extract using subCO2 soxhlet method was higher than the conventional sonication method and lower than the solvent extraction method. Overall, subCO2 soxhlet extraction of P. macrocarpa represents a promising method to produce organic solvent free and highly a-glucosidase inhibitory compounds containing extracts.